2021
DOI: 10.3390/nu13072366
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Evaluation of the Sepsis Triple Therapy High-Dose Vitamin C in Combination with Vitamin B1 and Hydrocortisone in a Human Peripheral Blood Mononuclear Cells (PBMCs) Model

Abstract: Sepsis is an extremely complex clinical syndrome, usually involving an excessive inflammatory response including an overshooting cytokine release that damages tissue and organs of the patient. Due to the severity of this condition, it is estimated that over 11 million people die from sepsis each year. Despite intensive research in the field, there is still no specific therapy for sepsis. Many sepsis patients show a marked deficiency of vitamin C. 9 out of 10 sepsis patients have a hypovitaminosis C, and every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Lactobacillus delbrueckii is one of the two probiotic strain constituents of the probiotic product used in this study ( Lacteol Forte [package insert], 2018 ). The results of the ex vivo study of Lauer et al (2021) support the findings of the significantly reduced MCP-1 level on day 6 within the HR-CB group. The average steady-state serum vitamin C concentration in the HR-CB group [0.4 mM, estimated based on dosing rate (1 g every 12 h), salt value (0.889), and clearance (0.92 L/h)] is within the range of vitamin C concentration as investigated in the Lauer et al study (0.2–2 mM) ( Lauer et al, 2021 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Lactobacillus delbrueckii is one of the two probiotic strain constituents of the probiotic product used in this study ( Lacteol Forte [package insert], 2018 ). The results of the ex vivo study of Lauer et al (2021) support the findings of the significantly reduced MCP-1 level on day 6 within the HR-CB group. The average steady-state serum vitamin C concentration in the HR-CB group [0.4 mM, estimated based on dosing rate (1 g every 12 h), salt value (0.889), and clearance (0.92 L/h)] is within the range of vitamin C concentration as investigated in the Lauer et al study (0.2–2 mM) ( Lauer et al, 2021 ).…”
Section: Discussionsupporting
confidence: 79%
“…Differently from this study, previous studies investigating the effects of interventions (CB and DP) on MCP-1 levels were either preclinical or clinical on patients without trauma (Dong et al, 2011;Alvarez et al, 2013;Lauer et al, 2021). The significantly reduced incidence of sepsis development by the end of the first week in both the HR-DP and HR-CB groups compared to the HR-C group was accompanied by a significant reduction in the proinflammatory chemokine MCP-1 level within these intervention groups compared to a significant increase within the control group.…”
Section: The Mcp-1 In the Current And Previous Studiesmentioning
confidence: 84%
“…Ascorbic acid (vitamin C) is a potent antioxidant that has been reported to provide protection against reactive oxygen species, preventing the damaging effects of oxidative stress, and it is also known for its anti-inflammatory role. [104,105] Previous studies have shown that ascorbic acid attenuates systemic inflammation induced by acute lung injury. [106] Likewise, oxoglutarate has been reported to have antioxidant properties and to play a key role in macrophage polarization into an M2 anti-inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a low EV cytokine response is presumed to reflect a suppressed in vivo (IV) "immune status" and has therefore frequently been proposed as a diagnostic tool to identify patients who might benefit from immunostimulatory therapy [13][14][15]. Furthermore, EV and in vitro stimulations of leukocytes are widely applied techniques in translational studies to investigate immunophysiological mechanisms or to test potential therapeutic interventions [16][17][18]. However, surprisingly little is known about whether these EV and in vitro models adequately reflect the IV situation.…”
Section: Introductionmentioning
confidence: 99%